EDUCATION AND PERSONNEL POLICY - V. Lukin; V. Korolyova (Вестник университета)
The questions of personnel policy in an education system, the stages of her formation promoting preservation, strengthening and development of personnel, strategy and tactics of rational use of the human capital are considered. Important element of personnel policy are questions of creation of system of management of information support. Subjects of its development, the principles, the purposes and the main directions, mechanisms of realization, the management and management are specied. Information support represents the multilevel system including tens of modules of a control system.